OVEREXPRESSION OPTIMIZATION OF FUSION OF P DOMAIN PROTEIN INTEGRATED HBSAG AND HBCAG EPITOPES IN ESCHERICHIA COLI BL21 (DE3) AS THE CANDIDATE FOR INTRANASAL HEPATITIS B VACCINE - Martdiyanti, Riesca
Hepatitis B is a viral infection that attacks the liver to cause acute and chronic diseases that are among the leading health problems in the world. The previous Hepatitis B vaccine reduced the level of infection in humans, but there is still a need to develop a safer and more effective hepatitis B vaccine. P particles from Norovirus are known to be potential candidates for subunit vaccines through intranasal administration. They have three loops on their surfaces that can be inserted by other antigens so that they have the potential to become dual vaccine candidates for Hepatitis B. In previous studies, successfully assembled and expressed P Domain-HBV proteins in vectors pET24a expression. However, protein expression is mostly present in the insoluble fraction (inclusion bodies). This study aimed to determine the optimum conditions of overexpression of soluble P domain-HBV protein in the pET24a plasmid vector in competent cells of Escherichia coli BL21 (DE3). The study conducted with variations in the concentration of IPTG 0.25mM, 0.50mM, 0.75mM, and 1mM; duration of induction for 3 hours, 4 hours, 6 hours and 16 hours with induction temperatures of 25oC and 37oC. Cell pellets resulting from overexpression were sonicated and analyzed the supernatant, total lysate, and protein aggregate by the SDS PAGE method. The optimum conditions are determined based on a multi-factorial design method. The model used in this analysis states that the results are significant (p-value <0.05), the statistical results of each optimization parameter indicate the significance of the optimization factors of temperature and induction duration (p-value = 0.001 and 0.028). The analysis results showed that the optimum protein expression condition was when the induction temperature was reduced to 25oC with the induction duration slowed to 16 hours, resulting in the highest percentage of protein solubility at 24.92% while there was no significant difference by the presence of IPTG inductor concentration parameters. Based on these results, it concluded that the duration and temperature influenced the expression of soluble P Domain-HBV protein in the expression vector Escherichia coli BL21 (DE3).